2020
DOI: 10.3390/ijerph18010238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Public Oral Health Services and Socioeconomic Indicators on the Frequency of Hospitalization and Deaths due to Oral Cancer in Brazil, between 2002–2017

Abstract: Background: Oral cancer is a frequent neoplasm worldwide, and socioeconomic factors and access to health services may be associated with its risk. Aim: To analyze effect of socioeconomic variables and the influence of public oral health services availability on the frequency of new hospitalized cases and mortality of oral cancer in Brazil. Materials and Methods: This observational study analyzed all Brazilian cities with at least one hospitalized case of oral cancer in the National Cancer Institute database (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 27 publications
1
25
0
6
Order By: Relevance
“…Our smaller HPV prevalence could be due to Brazil’s northern region having many cities surrounded by hydrographic access routes, which make it difficult to access health care. In addition, the distances between major urban areas and countryside cities are higher than in southern Brazil [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our smaller HPV prevalence could be due to Brazil’s northern region having many cities surrounded by hydrographic access routes, which make it difficult to access health care. In addition, the distances between major urban areas and countryside cities are higher than in southern Brazil [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological profile of the oral cancer disease consists of men, aged between 40 and 60 years ( 2 ), mostly with low socioeconomic status and low education ( 3 ). The main risk factors are smoking and alcohol abuse ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…A better prognosis can be achieved when the diagnosis is made early ( 10 ). However, the high rate of morbidity and mortality from oral cancer in Brazil is due to late hospitalization of patients in advanced stages of the disease ( 1 , 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies carried out in Brazil indicated that a good service structure is associated with better work processes in primary health care (PHC) 12 . Also, greater coverage of oral health services in PHC 13 and Dental Specialties Centers (acronym in Portuguese, CEO) 12 were associated with lower OC mortality rates. In Brazil, the National Oral Health Policy (acronym in Portuguese, PNSB) and the National Oncological Care Policy (acronym in Portuguese, PNAO) were implemented in 2004 and 2005, respectively, to articulate primary, specialized, and hospital care, organize a care line and reduce OC burden.…”
Section: Introductionmentioning
confidence: 99%